ENSURING OF RADIATION PROTECTION DURING WORKS ON TRANSFORMATION OF THE OBJECT SHELTER INTO ECOLOGICALLY SAFE SYSTEM. BIOPHYSICAL MONITORING OF THE PERSONNEL INTERNAL EXPOSURE DOSES - S. Yu. Nechaev; I. A. Likhtarev; V. B. Berkovski; L. N. Kovgan; Yu. V. Bonchuk; G. G. Ratia; P. B. Aryasov (Радиационная гигиена)
Given paper, states the ensuring of the interpretation of the basic radiation protection principles, relative to the works at the Object Shelter (OS). Analysis of the factors of radiation situation at the OS is figured out. Functioning at the present time individual dose monitoring (IDM) system at the OS is describe. The system is based on the methods of biophysical monitoring. A series of the results, obtained during internal exposure individual dose monitoring of the personnel is presented. It is mentioned, that implementation of the internal exposure dose biophysical monitoring system (during the works on transformation of the OS into ecologically safe system) allows:  provide adequate level of the IDM of the internal exposure dose (the level is corresponds to the present day requirements of the radiation protection); develop the recommendations on selection of individual means of protection of respiratory tract; ensure determination of the parameters of radioactive air contamination in the work areas; and, provide the optimal planning of dose load to the personnel.